Pengaruh Strategi Pemasaran dengan Teknik Tradisonal dan Online terhadap Hasil Penjualan - Nadhiroh Fardania; Sugeng Pradikto (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study explores the marketing strategies used by traders in Pasar Besar, Pasuruan City in dealing with changes in consumer behavior in the digital era. Data were obtained through semi-structured interviews and questionnaires, involving traders representing various types of products and marketing methods. Analysis was conducted qualitatively to explore key themes and quantitatively to identify patterns and trends. The results show that traditional marketing (direct selling) is still relevant because direct interaction creates emotional connections and increases buyer loyalty. However, this approach faces challenges due to the shift in buyer preferences to online shopping. Meanwhile, online marketing offers wider market reach, cost efficiency, and time flexibility, although its success is highly dependent on promotional capabilities and delivery management. The combination of traditional and online strategies has proven effective in reaching various buyer segments, providing significant sales increases. This approach requires careful planning to optimize the benefits of both methods without increasing operational costs. By understanding market needs and adjusting strategies, traders can maximize the potential of both approaches to achieve success amidst changing times.